Cryptosporidium sciurinum n. sp. (Apicomplexa: Cryptosporidiidae) in Eurasian Red Squirrels (Sciurus vulgaris) - Prediger, Jitka; Ježková, Jana; Holubová, Nikola; Sak, Bohumil; Konečný, Roman; Rost, Michael; McEvoy, John; Rajský, Dušan; Kváč, Martin (Microorganisms, 2021)
Cryptosporidium spp. are common protozoan pathogens in mammals. The diversity and biology of Cryptosporidium in tree squirrels are not well studied. A total of 258 Eurasian red squirrels (Sciurus vulgaris) from 25 and 15 locations in the Czech Republic and Slovakia, respectively, were examined for Cryptosporidium spp. oocysts and specific DNA at the SSU, actin, HSP70, TRAP-C1, COWP, and gp60 loci. Out of 26 positive animals, only juveniles (9/12) were microscopically positive (18,000 to 72,000 OPG), and molecular analyses revealed the presence of Cryptosporidium sp. ferret genotype in all specimens. Oocysts obtained from naturally-infected squirrels measured 5.54-5.22 μm and were not infectious for laboratory mice (BALB/c and SCID), Mongolian gerbils, Guinea pigs, Southern multimammate mice, chickens, or budgerigars. None of naturally infected squirrels showed clinical signs of disease. The frequency of occurrence of the ferret genotype in squirrels did not vary statistically based on host age, gender or country of capture. Phylogenetic analysis of sequences from six loci revealed that Cryptosporidium sp. ferret genotype is genetically distinct from the currently accepted Cryptosporidium species. Morphological and biological data from this and previous studies support the establishment of Cryptosporidium sp. ferret genotype as a new species, Cryptosporidium sciurinum n. sp.
Keywords: oocyst size; course of infection; phylogeny; infectivity; biology; occurrence; Cryptosporidium sp. ferret genotype